2022
DOI: 10.4103/jehp.jehp_1752_21
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic bacteriuria of pregnant women in a tertiary care centre

Abstract: BACKGROUND: Asymptomatic bacteriuria (ASB) is commonly seen during pregnancy due to the various morphological, hormonal, and physiological changes the body undergoes. If left undiagnosed, it can lead to conditions such as pyelonephritis and preterm delivery which could culminate in causing maternal and fetal morbidity and mortality. Therefore, this study aims to determine the prevalence, risk factors, microbial profile, and antibiotic susceptibility patterns associated with ASB in a tertiary healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
1
3
0
1
Order By: Relevance
“…Nitrofurantoin and trimethoprim-sulfamethoxazole showed high efficacy across all bacterial strains, similar to the findings of Totadhri et al [ 18 ]. Lower sensitivity to other antibiotics can be attributed to empirical use [ 19 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nitrofurantoin and trimethoprim-sulfamethoxazole showed high efficacy across all bacterial strains, similar to the findings of Totadhri et al [ 18 ]. Lower sensitivity to other antibiotics can be attributed to empirical use [ 19 ].…”
Section: Discussionsupporting
confidence: 89%
“…Escherichia coli was the most prevalent strain found in this study. Several studies have reported it to be the most common [ 17 , 18 ]. This phenomenon may be attributed to the common occurrence of urinary stasis during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Pola bakteri pada penelitian ini sama dengan hasil penelitian yang dilaporkan Mohebi ., dkk di India, dari 150 sampel penelitian didapatkan delapan pasien yang mempunyai hasil kultur urin positif. Escherichia coli merupakan penyebab terbanyak (45%), diikuti Klebsiella pneumoniae, Coagulase negative staphylococcus (CONS), Candida albicans, dan Group B Streptococcus (Mohebi dkk., 2018). Escherichia coli merupakan penyebab terbanyak bakteriuria asimtomatis pada penelitian di Arab Saudi yaitu 44,26%, Group B Streptococcus 23,77%, Klebsiella pneumoniae 15,57%, dan Enterococcus faecalis 9,02% (Alshamlan dkk., 2022).…”
Section: Pola Mikroba Penyebab Bakteriuria Asimtomatisunclassified
“…Understanding the susceptibility of GBS to antibiotics can guide the selection of clinical treatment ( Husen et al, 2023 ). Commonly used antibiotic susceptibility testing methods include: disc diffusion method ( Totadhri et al, 2022 ), where paper discs containing different antibiotics are placed on a culture medium to observe the relationship between bacterial growth and inhibition zones; broth dilution method ( Stepanović et al, 2003 ), which gradually dilutes different concentrations of antibiotics in a culture medium to observe the minimum inhibitory concentration; E-test ( Persson et al, 2008 ), which uses a gradient concentration of antibiotics on a strip to observe the relative position between bacterial growth and inhibition zones. These methods can be used to determine the susceptibility of GBS to a specific antibiotic, helping doctors choose appropriate drugs for treatment.…”
Section: Introduction Of Gbsmentioning
confidence: 99%